Seroprevalence of RSV antibodies in a contemporary (2022-2023) cohort of adults - Lara I. Teodoro; Inna G. Ovsyannikova; Diane E. Grill; Gregory A. Poland; Richard B. Kennedy (International Journal of Infectious Diseases, 2025)
Objectives: Respiratory syncytial virus (RSV) infection may cause serious illness and mortality in older adults (≥65 years). This study aimed to assess the seroprevalence of anti-RSV IgG antibodies in adults from a United States cohort and compare antibody levels among individuals with a history of recent RSV vaccination or infection. Methods: A total of 475 subjects (ages 27-99) were randomly selected from the Mayo Clinic Biobank’s residual sera repository (2022-2023). Samples were tested for anti-RSV IgG using an enzyme-linked immunosorbent assay (ELISA). Additional cohorts included individuals with documented RSV infection (n = 40) or recent RSV vaccination (n = 71). Results: Among the seroprevalence cohort, 83.8% tested RSV IgG positive against RSV-A whole virus antigen. Males had significantly higher antibody titers than females (P < 0.001), and antibody titers increased post-RSV season (p = 0.02). Compared to the general cohort, RSV-seropositivity rates were higher in recently diagnosed (97.5%) and vaccinated (95.8%) individuals. Conclusions: This study demonstrates a high seroprevalence of RSV-A IgG in adults, with variations across sex and seasonality, and corroborates waning immunity following RSV infection. Recent infection or vaccination significantly boosts antibody levels, reinforcing the importance of continued surveillance of RSV immunity.